Federalism and decentralization in the contemporary Middle East and North Africa - Bâli, Aslı Ü. 1971-; Dajani, Omar M. 1970- (ASCL studies in comparative law, 2023)
"This book is for anyone interested in alternatives to conventional understandings of the MENA region, with a view towards identifying practical solutions to the longstanding problems of authoritarian governance and ethnic conflict"--